Desain Penataan Lahan Pasca Tambang Rakyat Di Desa Tanjung Riu Kabupaten Gunung Mas Provinsi Kalimantan Tengah - Noby Ade Yusevi; Emmy Sri Mahreda; Rizqi Puteri Mahyudin; Kissinger Kissinger (EnviroScienteae, 2021)
Mining is a series of activities of exploring, mining (excavation), processing, utilization and marketing of minerals (minerals, coal, geothermal, oil and gas). Gunung Mas Regency, especially Tanjung Riu Village, Kurun Subdistrict, is one of the places in Central Kalimantan Province which has mineral resources including primary and secondary gold, zircon, iron ore and coal. People’s mining activities, especially gold mining in Tanjung Riu Village, are increasingly being carried out by the people and are further away from road access. This causes the people's mining area become increasingly depleted, so that in mining closure, it leaves the formation of critical land that is not organized and is not in accordance with the function of the surrounding environment and cannot be utilized. Most of the critical lands are in the form of void pits have the potential to cause various contimination, such as decreasing the quality of water stored in the voids due to metal contamination and decreasing the pH value of the water so that the water becomes acidic. The description above becomes the basis for research on the design mining closure of people‘s mining area in Tanjung Riu Village, Kurun District, Gunung Mas Regency. This design will be able to make the land useful again both for the People around the research location and for the general public whose use of the ex people’s mining area.